Essential fatty acids and ascorbic acid- interactions and effects on melanoma growth - Gardiner, Neil Stockenstrom (Rhodes University, Faculty of Science, Department of Chemistry, 1990)
The present study was carried out to determine the effects and possible mechanisms of action of the essential fatty acids (EFAs) (linoleic acid (LA), gamma-linolenic acid (GLA) and arachidonic acid (AA)) and ascorbic acid (Asc) on BL6 murine melanoma growth in cell culture and in mice. Interactions between the nutrients in influencing melanoma growth as well as possible mechanisms of the interactions were also examined in the above systems. Cell culture studies revealed that all three EFAs (0-SOÎ¼g/ml) and Asc (0-200Î¼g/ml) significantly inhibited melanoma growth at the concentrations used. The EF As were also found to significantly inhibit growth, although to a lesser extent than BL6 cells, of monkey kidney (LLCMK) cells which were used as a non-malignant control cell line. Asc in contrast was found not to inhibit growth of these cells. Supplementation of Asc (lOO)Î¼g/ml) to EFA containing (0-50Î¼g/ml) medium was found to significantly increase inhibition of cell growth in both cell lines, and in the BL6 cells in particular, after taking into account the growth inhibitory effects of Asc in the absence of EFAs. The mechanism of cell growth inhibition by the EF As appeared to involve lipid peroxidation but not enhanced prostaglandin (PG) or leukotriene (LT) synthesis. While Asc was found to increase both lipid peroxidation and PG synthesis in the cells, these mechanisms and enhanced LT synthesis did not appear to have played a role in the inhibition of cell growth by Asc or in the growth inhibitory interaction between Asc and the EF As. In vivo studies revealed that diets containing essential or polyunsaturated fatty acids (EFAs/PUFAs) in the form of vegetable oils, and in particular GLA in the form of evening primrose oil, significantly promoted melanoma growth in mice when compared with an EFA/PUFA free diet containing predominantly saturated fats (SF). Supplementary dietary Asc in contrast was found to significantly inhibit melanoma growth in mice fed EFA/PUFA, and in particular GLA, containing diets but not in mice fed SF cont~g diets. This result appears to indicate the occurrence of an interaction between the two nutrients. Ul The mechanism of tumour promotion by the EP As/PUP As did not appear to have involved enhanced PG or LT synthesis or lipid peroxidation. Since dietary EPA/PUPA manipulation was found to significantly alter the EPA content of tissues, including the melanomas, the mechanism of tumour promotion may have involved changes in the EPA composition of the tumour cells. While supplementary Asc was found to significantly increase the Asc content of certain tissues, including the melanomas, which may have played a role in tumour growth inhibition by Asc, it was found not to affect the EPA content of tissues. Enhanced PG or LT synthesis and lipid perox:idation did not appear to have been involved in the tumour growth inhibitory interaction between Asc and the EP As/PUP As. THe activity of the enzyme delta-6-desaturase, a key enzyme in EF A metabolism which catalyses the desaturation of LA to GLA, and the influence of Asc on activity of the enzyme were also examined. The cultured cells, and BL6 cells in particular, were found to contain significant activity of the enzyme. Whereas murine liver microsomal fractions were found to contain delta-6-desaturase activity, microsomes from melanomas grown in mice were found to lack activity of the enzyme. The significant tumour promoting effects of the GLA containing EPO diet may have been the result of the lack of delta-6-desaturase activity in tumour cells grown in mice. Asc was found to stimulate activity of the enzyme in cultured BL6 cells but not in LLCM.K cells, while dietary Asc and EF A/PUP A manipulation did not influence activity of the enzyme in microsomal fractions. This study has confirmed previous reports of the in vivo tumour promoting effects of dietary EP As/PUP As and the tumour growth inhibitory effects of Asc. The in vitro cell growth inhibitory effects of Asc and the EP As also confirm the results of previous reports. Previous studies investigating possible interactions between Asc and EP As/PUP As in influencing tumour cell growth could not be located in the relevant literature. This study may therefore be one of the first investigations of any such interaction between these nutrients in tumour cells. While this study was not able to identify the mechanisms involved in the different tumour promoting or tumour growth inhibitory effects of the two nutrients in the two systems, it did eliminate a number of potential mechanisms. The results of this study also emphasise the difficulty of attempting to compare the results of in vitro and in vivo studies.
Keywords: Fatty acids; Melanoma; Mice -- Diseases